Geographical variation in colour of female threespine stickleback (Gasterosteus aculeatus) - French, Connor M.; Ingram, Travis; Bolnick, Daniel I. (PeerJ, 2018)
The ecological multifunctionality of colour often results in multiple selective pressures operating on a single trait. Most research on colour evolution focuses on males because they are the most conspicuous sex in most species. This bias can limit inferences about the ecological drivers of colour evolution. For example, little is known about population divergence in colour of female threespine stickleback (Gasterosteus aculeatus), which is among the most intensively-studied model vertebrates in evolution, ecology, and behaviour. In contrast, the evolution and ecology of colour in male stickleback has received considerable attention. One aspect of female colouration that is lacking previous research is non-ornamental body colour. Non-ornamental colour can play defensive and social roles, and indicate other aspects of female stickleback ecology. To remedy this knowledge gap, we measured the colour and brightness of one dorsal and one ventral lateral area on female stickleback from nine lake populations on Vancouver Island. We found that lake populations varied in overall colour brightness and dorso-ventral contrast. In addition, we found that female brightness increased with lake size, indicating potential ecological drivers of these colour differences. Our results demonstrate that there is substantial scope for future research on female colour diversification, which has been overlooked because past researchers focused on dramatic male nuptial colours.
Keywords: Female; Colour; Selection; Stickleback; Geography